Efektivitas Berkumur Air Rebusan Kulit Manggis (Garcinia mangostana Linn) Dalam Menurunkan Debris Indeks Pada Remaja - Adam, Jeanne d’Arc Zafera; Koch, Novarita M; Tahulending, Anneke A; Karamoy, Youla; Sumampouw, Oksfriani Jufri (Jurnal Ners, 2024)
The skin of the mangosteen fruit (Garcinia mangostana Linn.) contains higher pharmacological properties than other parts of the mangosteen fruit as antibacterial, anti-inflammatory, antioxidant and anticancer. Some studies show that a decoction of mangosteen peel can lower the debris index. The purpose of the study was to determine the effectiveness of gargling mangosteen peel boiled water on reducing the debris index in adolescents in the city of Manado. This is an experimental research with a one-group pretest-posttest approach. The study was conducted at SMP Negeri 8 Manado in April 2024 on 80 respondents. The instruments of this study are oral diagnostic tools, mangosteen peel boiled water ingredients and debris index assessment format. Analysis results through Wilcoxson statistical tests. The results showed that the positive ranks or difference between pretest and postest effectiveness of gargling mangosteen peel boiled water against the decrease in debris index obtained a negative ranks value of 62, meaning that out of 80 respondents there were 62 respondents who experienced a decrease in index debris with a mean rank of 31.50. In addition, a value of p = 0.000 (p <0.05) was obtained so that it was stated that a significant difference in the debris index value was obtained on the pretest and posttest. It can be concluded that gargling with boiled water of mangosteen peel is effective in reducing the debris index in adolescents in Manado city.